2017
DOI: 10.1364/oe.25.011760
|View full text |Cite
|
Sign up to set email alerts
|

Class-A operation of an optically-pumped 16 µm-emitting quantum dash-based vertical-external-cavity surface-emitting laser on InP

Abstract: A continuous-wave 1.6 µm-emitting InAs Quantum Dash-based Optically-Pumped Vertical-External-Cavity Surface-Emitting Laser on InP is demonstrated. The laser emits in the L-band with a stable linear polarization. Up to 163 mW output power has been obtained in multi-transverse mode regime. Single-frequency regime is achieved in the 1609-1622 nm range, with an estimated linewidth of 22 kHz in a 49 mm cavity, and a maximum emitted power of 7.9 mW at 1611 nm. In such conditions, the laser exhibits a Class-A behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 23 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…Very recently, Pes et al utilized Gas Source MBE in growing a 6-stack InAs Qdashes of 3 sets on a (001) InP substrate [34]. Each Qdash layer was separated by a In 0.8 Ga 0.2 As 0.435 P barrier layer of a thickness of 15-nm and surrounded by quaternary alloy layers whose thickness was chosen to ensure a homogenous excitation of the active region.…”
Section: Inas/ingaasp Materials Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Very recently, Pes et al utilized Gas Source MBE in growing a 6-stack InAs Qdashes of 3 sets on a (001) InP substrate [34]. Each Qdash layer was separated by a In 0.8 Ga 0.2 As 0.435 P barrier layer of a thickness of 15-nm and surrounded by quaternary alloy layers whose thickness was chosen to ensure a homogenous excitation of the active region.…”
Section: Inas/ingaasp Materials Systemmentioning
confidence: 99%
“…The slope efficiency was estimated as 0.32 W/A whilst the threshold current density was obtained as w4 kA/cm 2 . Very recently, Pes et al [34] reported a continuouswave 1.6 mm-emitting optically-pumped InAs Qdash based vertical-external-cavity surface-emitting laser. In multi-transverse mode operation, the maximum output power was measured as 163 mW at 20 C from 12 mm-long cavity whereas when the laser was made single-frequency, the maximum measured output power was 7.9 mW at 19.5 C in a 49 mm-long cavity.…”
Section: Inas/ingaasp/inp Qdash Lasersmentioning
confidence: 99%